Mangifera indica L. Leaves as a Potential Food Source of Phenolic Compounds with Biological Activity - Giuseppe Sferrazzo; Rosa Palmeri; Cristina Restuccia; Lucia Parafati; Laura Siracusa; Mariarita Spampinato; Giuseppe Carota; Alfio Distefano; Michelino Di Rosa; Barbara Tomasello; Angelita Costantino; Massimo Gulisano; et al. (Antioxidants, 2022)
It is well recognized that functional foods rich in antioxidants and antiinflammation agents including polyphenols, probiotics/prebiotics, and bioactive compounds have been found to have positive effects on the aging process. In particular, fruits play an important role in regular diet, promoting good health and longevity. In this study, we investigated on biological properties of extract obtained from Mangifera indica L. leaves in preclinical in vitro models. Specifically, the profile and content of bioactive compounds, the antimicrobial potential toward food spoilage and pathogenic bacterial species, and the eventually protective effect in inflammation were examined. Our findings revealed that MLE was rich in polyphenols, showing a content exclusively in the subclass of benzophenone/xanthone metabolites, and these phytochemical compounds demonstrated the highest antioxidant capacity and greatest in vitro antibacterial activity toward different bacterial species such as Bacillus cereus, B. subtilis, Pseudomonas fluorescens, Staphylococcus aureus, and St. haemolyticus. Furthermore, our data showed an in vitro anti-inflammatory, antioxidant, and antifibrotic activity.